Alternative BRAF mutations in BRAF V600E‐negative hairy cell leukaemias. (16th January 2014) - Tschernitz, Sebastian; Flossbach, Lucia; Bonengel, Margrit; Roth, Sabine; Rosenwald, Andreas; Geissinger, Eva
Summary The BRAF V600E mutation in exon 15 is considered the disease‐defining mutation in hairy cell leukaemia (HCL), but single HCL cases lacking this mutation have been described. In 24 HCL, as well as in 194 various mature B‐ and T‐cell neoplasms, we extended the search for BRAF mutations to exon 11. Two V600E‐negative HCL contained novel, potentially functionally relevant mutations in exon 11 (F468C and D449E), while one other HCL was BRAF wild‐type in exons 2–17. All non‐HCL lymphomas lacked BRAF mutations. We therefore suggest screening of BRAF V600E‐negative HCL for alternative exon 11 mutations in the diagnostic setting.